Battery energy storage system optimal sizing in a battery electric vehicle fast charging infrastructure - Félix, Pedro Miguel Cardoso (2020)
The growing number of battery electric vehicles and plug-in hybrid electric vehicles brings the need of more fast charging stations across cities and highway stops. This charging stations toned to be connected to the electrical grid via existent facilities, causing constraints such as power availability. This work brings an approach for the planning and operation of such energy hubs by coping with this challenge by deploying a Battery-based Energy Storage System (BESS). With the BESS integration, it is expected to minimize utilization and overall energy costs, preventing infrastructure upgrades, and enhancing the integration of renewable energy resources. This approach sizes a stationary energy storage system with lithium-ion technology batteries through a co-optimization of the planning and operation stages, integrated into an electrical installation that will implement fast charging stations. This sizing is a result of an optimization based on the interior point algorithm, where the objective is to minimize the costs of maintenance, operation, and installation of a BESS, while properly modelling the different resources such as the BESS, the charging station and Electric Vehicles (EV) charging and Photovoltaic generation (PV). In order to have an estimate of necessary power and energy consumption, a simulated frequency of parking of BEVs at the charging stations, based on probabilities, was modelled taking into account the distance that a battery electric vehicle will do in a certain period of time and the probability of being a car with a particular set of characteristics.